2018
DOI: 10.36456/abadimas.v2.i1.a1617
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Penanganan Terhadap Anak Berkebutuhan Khusus

Abstract: Anak-anak dengan kebutuhan khusus adalah anak-anak cacat atau hambatan fisik, mental, intelektual, sosial, atau emosional, seperti: anak-anak dengan autisme, tuli, buta, retradasi mental, cacat fisik dan lain-lain dapat memiliki pengaruh yang signifikan terhadap proses pertumbuhan atau perkembangan dibandingkan dengan anak-anak lain seusianya. Jika kondisi ini tidak ditangani dengan baik, perkembangan kemampuan anak mengalami kendala dan beban orang tua, keluarga, masyarakat dan negara. Tujuan penanganan yang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
0
4
0
11
Order By: Relevance
“…So, it is hoped that this study can be an insight for inclusive schools to overcome slow learner problems, especially in terms of concentration, memory and impulsiveness by providing Islamic therapy. [5] found that therapy is a treatment given by experts to children with special needs in various aspects. The purpose of therapy was to help children with special needs in improving various aspects such as in the academic field so that children were able to participate in learning activities well, then in the social field so that children could socialize with their peers and the surrounding community and in the emotional field so that children could dispense emotions into their positive things.…”
Section: Problem Of Studymentioning
confidence: 99%
“…So, it is hoped that this study can be an insight for inclusive schools to overcome slow learner problems, especially in terms of concentration, memory and impulsiveness by providing Islamic therapy. [5] found that therapy is a treatment given by experts to children with special needs in various aspects. The purpose of therapy was to help children with special needs in improving various aspects such as in the academic field so that children were able to participate in learning activities well, then in the social field so that children could socialize with their peers and the surrounding community and in the emotional field so that children could dispense emotions into their positive things.…”
Section: Problem Of Studymentioning
confidence: 99%
“…Dan beberapa orang tua memang sudah mengetahui masalah mental yang anak miliki, dan sudah mengetahui bahwa anaknya berkebutuhan khusus. Menurut William Cruickshank dan G. Orville Jonhson pada bukunya menjelaskan bahwa ABK (anak berkebutuhan khusus) adalah mereka yang mempunyai kelainan psikologis, sosial, emosional dan intelektual yang memerlukan pembelajaran khusus (Purba Bagus Sunarya et al, 2018). Sehingga pemantauan sosial emosional anak menggunakan kuesioner masalah mental emosional (KMME) perlu diperhatikan oleh para orang tua untuk melihat anak memiliki masalah emosional atau tidak.…”
Section: Nounclassified
“…Hal tersebut terlihat anak kurang mampu melakukan pekerjaan-pekerjaan yang sesuai dengan seusianya. Selain gangguan dalam perkembangan mental dan sosial, anak-anak dengan kondisi tunagrahita mengalami kesulitan mengingat apa yang telah mereka lihat dan dengar, yang mengakibatkan kesulitan bicara atau komunikasi dengan orang lain (Purba Bagus Sunarya et al, 2018).…”
Section: Pendahuluanunclassified